Description of the preimaginal instars and redescription of the adult stage of Belostoma elongatum Montandon (Hemiptera: Belostomatidae) - de Reyes, Cristina A.; Estévez, Ana L.; Schnack, Juan A. (Zootaxa, 2006)
The five instars of Belostoma elongatum Montandon are described and figured. Immature specimens were obtained from eggs carried by an incubating male of this species captured at San Cosme, Corrientes Province, Argentina (27 o 28’ S, 58 o 50 W). Thirtyfive emerged individuals were reared in the laboratory from the first stadium.